Antiviral Treatment against Monkeypox: A Scoping Review - Ortiz-Saavedra, Brando (2022)
During the COVID-19 pandemic, the increase in reports of human monkeypox virus infection cases spreading in many countries outside Africa is a major cause for concern. Therefore, this study aimed to explore the evidence of antiviral pharmacotherapy available for the treatment of adult patients with monkeypox. A scoping review of the literature was conducted using PubMed, Scopus, Web of Science, Embase, and CENTRAL databases until 12 September 2022. The key search terms used were “monkeypox” and “treatment”. A total of 1927 articles were retrieved using the search strategy. After removing duplicates (n = 1007) and examining by title, abstract, and full text, 11 studies reporting case reports of monkeypox with antiviral treatment were included, detailing the number of monkeypox cases, clinical manifestations, number of participants with antiviral treatment, history of sexually transmitted diseases, method of diagnosis, location of skin lesions, drugs used in antiviral treatment, route of administration, and outcome. A total of 1281 confirmed cases of monkeypox have been reported, of which 65 monkeypox cases had antiviral treatment distributed most frequently in the United States (n = 30), the United Kingdom (n = 6), and Spain (n = 6). Of the total cases, 1269 (99.1%) were male with an age range of 18 to 76 years, and 1226 (95.7%) had a sexual behavior of being men who have sex with men. All confirmed cases of monkeypox were diagnosed by reverse transcriptase polymerase chain reaction (RT-PCR). The most frequent clinical manifestations were skin lesions, fever, lymphadenopathy, headache, fatigue, and myalgia. The most frequent locations of the lesions were perianal, genital, facial, and upper and lower extremities. The most commonly used drugs for antiviral treatment of monkeypox were: tecovirimat, cidofovir, and brincidofovir. All patients had a complete recovery. According to current evidence, the efficacy and safety of antiviral drugs against monkeypox is of low quality and scarce.